TINGKAT PENGETAHUAN DAN SIKAP TENTANG CUCI TANGAN PAKAI SABUN (CTPS) PADA SISWA SDN BATUAH I DAN BATUAH III PAGATAN - Ratna Setyaningrum; Achmad Rofi’i; Annisa Setyanti (Jurnal Berkala Kesehatan, 2015)
Abstract One indicator of healthy and clean life behaviour is hand washing with soap. Habits of  Indonesian community in hand washing with soap is still relatively low, the indication can be seen by the high prevalence of diarrheal disease. Hand washing with soap focus is school student as "Agent of Change". The aim of this study is to describe the level of knowledge and attitude about hand washing with soap among student in Batuah I and Batuah III Public Elementary School Pagatan. This is a descriptive study with cross-sectional design. The subject are student of class V in Batuah I and Batuah III Public Elementary School Pagatan as many as 60 students. The result show that the level of knowledge about hand washing with soap majority in good category as many as 86, 67% in Batuah I Public Elementary School and as many as 76.67% in Batuah III Public Elementary School Pagatan. The attitude of respondents about hand washing with soap majority in good category as many as 83.33% in Batuah I and Batuah III Public Elementary School Pagatan. Keywords: knowledge, attitude, hand washing with soap, elementary student